Monocytes presenting a pro-inflammatory profile persist in patients submitted to a long-term pharmacological treatment after acute myocardial infarction - de Carvalho, Daniel Carneiro; Fonseca, Francisco Antonio Helfenstein; Izar, Maria Cristina de Oliveira; Silveira, Ana Luíza Pereira Assunção; Tuleta, Izabela Dorota; do Amaral, Jônatas Bussador; Neves, Lucas Melo; Bachi, André Luis Lacerda; França, Carolina Nunes (Frontiers in Physiology, 2023)
Introduction: Although it is broadly known that monocyte recruitment is involved in atherosclerosis development and that, in accordance with the microenvironment, these cells can be modulated into three well-known subpopulations: Classical (CD14++CD16−), intermediate (CD14++CD16+), and non-classical (CD14+CD16++), the effects of treatment with different pharmacological strategies (based on lipid-lowering and antiplatelets) after acute myocardial infarction upon the monocytes modulation and the role of the chemokine receptors CCR2, CCR5 and CX3CR1 in this context, are poorly understood. Methods: In this study, patients [n = 148, both men (n = 105, 71%) and women (n = 43, 29%)] submitted to treatment with a 2×2 factorial design, in which they received rosuvastatin 20 mg or simvastatin 40 mg plus ezetimibe 10 mg, as well as ticagrelor 90 mg or clopidogrel 75 mg were enrolled. Monocyte subsets were analyzed by flow cytometry at baseline (BL), and after one (1-M) and 6 months (6-M) of treatment. Results: Firstly, our results showed that, regardless of the treatment received, higher percentages of classical monocytes and lower of non-classical monocytes were found at the 6-M time point than BL values, whilst the percentage of intermediate monocytes was higher in all time points assessed than the other subsets. There were reductions in the CCR2 expression by non-classical and intermediate monocytes, without differences for the classical subtype. Concerning the CCR5 expression, there were reductions in the three monocyte subtypes, whereas the CX3CR1 expression increased both in intermediate and classical monocytes, without differences for non-classical monocytes. In relation to the treatment received, a higher percentage of intermediate monocytes at the 6-M time point than the values BL was observed in the group treated with simvastatin + ezetimibe + clopidogrel. No significant differences were found concerning non-classical, intermediate, and classical monocytes, for CCR2, CCR5, and CX3CR1 in the four treatment arms. Conclusion: Taken together, our results demonstrated that even under lipid-lowering and antiplatelet therapy for 6 months, the inflammatory phenotype of monocytes still persisted in the patients enrolled in this study.